Hierarchical core/shell structure of MnO2@polyaniline composites grown on carbon fiber paper for application in pseudocapacitors. Issue 44 (21st October 2015) - Yang, MinHo; Hong, Seok Bok; Choi, Bong Gill
Abstract : Hierarchical core/shell structured arrays of MnO2 @polyaniline nanosheets synthesized on the surface of carbon fiber paper, showed high specific capacitance, high rate capability, and good cycle life. Abstract : Hierarchical core/shell structured arrays of MnO2 @polyaniline (PANI) nanosheets are successfully deposited on the surface of carbon fiber paper (CFP) by a two-step method of a redox reaction-assisted deposition of MnO2 and post electrodeposition of PANI. The CFP is used as a three-dimensional (3D) current collector to ensure 3D transport of ions and electrons with a large surface area. In addition, the electrodeposition technique enables conformal and thin coating of a layer of PANI across the entire MnO2 nanosheet. The MnO2 @PANI on the CFP shows a unique architecture for efficient ion diffusion pathways in hierarchical porous structures and rapid electron transfer through PANI coated layers. The MnO2 @PANI/CFP can be applied as a binder- and carbon-free electrode for supercapacitors. Evaluation of the electrochemical performance revealed that the as-prepared electrodes have a high value of specific capacitance (437 F g −1 at 1 A g −1 ), high rate capability (62.4% retention at 15 A g −1 ), and good cycle life (∼100% at sequential current densities of 1 and 5 A g −1 over 3000 cycles).